Sound Change as Media for Showing Deference - Oktiva Herry Candra (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
AbstractJavanese language shows a dynamic change when used in daily communication. The change represented by vowels and consonants as a speaker alternates from Ngoko to Krama is not only a phenomenon of phonetics but also a phenomenon of intention. A speaker changes his linguistic code to meet social functions of language. One of them is that the change of phoneme represents the way of Javanese people when they give respect or honor to others. Phonetically, the change of phoneme will result in different mouth shapes as these phonemes are produced. According to Javanese, the shape of mouth is in line with politeness. The participatory observation method was applied to get the data. The result shows that indeed there are various changes in vowel and consonants when a speaker alternates from Ngoko to Krama. This alternation is in line with the change in which language sound tends to change from open to close. It seems Javanese will use frontier vowels and consonant as they want to obey politeness principle.     Key words: vowel and consonant change, shape of mouth and politeness